Development and application of an uncapped mRNA platform - Xiaodi Zheng; Biao Liu; Peng Ni; Linkang Cai; Xiaotai Shi; Zonghuang Ke; Siqi Zhang; Bing Hu; Binfeng Yang; Yiyan Xu; Wei Long; Zhizheng Fang; et al. (Annals of Medicine, 2025)
Background A novel uncapped mRNA platform was developed.Methods Five lipid nanoparticle (LNP)-encapsulated mRNA constructs were made to evaluate several aspects of our platform, including transfection efficiency and durability in vitro and in vivo and the activation of humoral and cellular immunity in several animal models. The constructs were eGFP-mRNA-LNP (for enhanced green fluorescence mRNA), Fluc-mRNA-LNP (for firefly luciferase mRNA), SδT-mRNA-LNP (for Delta strain SARS-CoV-2 spike protein trimer mRNA), gDED-mRNA-LNP (for truncated glycoprotein D mRNA coding ectodomain from herpes simplex virus type 2 (HSV2)) and gDFR-mRNA-LNP (for truncated HSV2 glycoprotein D mRNA coding amino acids 1–400).Results Quantifiable target protein expression was achieved in vitro and in vivo with eGFP- and Fluc-mRNA-LNP. SδT-mRNA-LNP, gDED-mRNA-LNP and gDFR-mRNA-LNP induced both humoral and cellular immune responses comparable to those obtained by previously reported capped mRNA-LNP constructs. Notably, SδT-mRNA-LNP elicited neutralizing antibodies in hamsters against the Omicron and Delta strains. Additionally, gDED-mRNA-LNP and gDFR-mRNA-LNP induced potent neutralizing antibodies in rabbits and mice. The mRNA constructs with uridine triphosphate (UTP) outperformed those with N1-methylpseudouridine triphosphate (N1mψTP) in the induction of antibodies via SδT-mRNA-LNP.Conclusions Our uncapped, process-simplified and economical mRNA platform may have broad utility in vaccines and protein replacement drugs.KEY MESSAGESThe mRNA platform described in our paper uses internal ribosome entry site (IRES) (Rapid, Amplified, Capless and Economical, RACE; Register as BH-RACE platform) instead of caps and uridine triphosphate (UTP) instead of N1-methylpseudouridine triphosphate (N1mψTP) to synthesize mRNA.Through the self-developed packaging instrument and lipid nanoparticle (LNP) delivery system, mRNA can be expressed in cells more efficiently, quickly and economically.Particularly exciting is that potent neutralizing antibodies against Delta and Omicron real viruses were induced with the new coronavirus S protein mRNA vaccine from the BH-RACE platform.